The phenomenon of the recruitment of children and adolescents by illegal organized armed groups : case of Colombia. - Mendoza Tovar, Víctor Hugo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This essay succinctly shows the dynamics derived from the internal armed conflict in Colombia and the strategic value of the illegal economy where the number of children and adolescents (children and adolescents) who are used by illegal armed groups for intelligence work, remittances, sexual servitude, manufacture and installation of anti-personnel mines, among others, is increasing every day. The Peace Treaty signed in 2016 by the Colombian State and the FARC guerrilla allowed for a reduction in the recruitment of children and adolescents; however, the increase in the number of ex-FARC dissidents and Organised Armed Groups (GAO) present in the national territory, have once again used recruitment as an internal policy to expand the ranks of combatants and their criminal activities, even though International Humanitarian Law (IHL) and national and international jurisprudence prohibit it. The methodology used in this academic research is descriptive with a qualitative approach, in which the regulations and international jurisprudence framed in the International Humanitarian Law of armed conflicts and the Universal Declaration of Human Rights are enunciated, aiming to make an x-ray on the phenomenon of recruitment of children and adolescents in Colombia, being this document an input document for consultation in the study and achievement of research of a social nature, where social phenomena are addressed.